Effects of Dietary Levels of Methionine on Broiler Performance and Carcass Characteristics - Ahmed, Mohamed Elamin; Abbas, Talha E. (International Journal of Poultry Science, 2011)
The present experiment was carried out to determine the effect of dietary methionine levels higher than NRC recommendation on broiler performance and carcass traits. Four dietary levels of methionine 0, 100, 120 and 130% of NRC recommendation were used. Dietary levels of methionine, expressed as percentage of NRC recommendations, significantly (p